Incorporation of thermally labile additives in polyimide carbon membrane for hydrogen separation - Norazlianie, Sazali; W. N. W., Salleh; A. F., Ismail; Iwamotoe, Yuji (Elsevier, 2021)
In this study, three thermally labile additives microcrystalline cellulose (MCC), nanocrystalline cellulose (NCC), and polyvinylpyrrolidone (PVP) were introduced to the P84-copolyimide (PI) solution. PI-based carbon tubular membranes were fabricated using dip-coating method, followed by sample characterizations in order to determine their structural morphologies, thermal stability and gas permeation performance. NCC was added as the membrane pore former for the hydrogen gas (H2) separation. While tests involving pure H2 and N2 permeation were carried out at room temperature, carbon membranes were carbonized at a final temperature of 800 °C, with the heating rate of 3 °C/min under the Ar flow. Excellent result of H2/N2 selectivity was obtained with value of 430.06 ± 4.16. Addition of NCC has significantly increased the number of pore channels in the membrane, hence, contributing to high gas permeance and selectivity. NCC has shown potential as a good additive for an enhanced hydrogen separation performance.